Analisis Konflik Ekologi Politik dalam Pembangunan Waduk Jatigede (Jurnal Nawala Politika, 2022)
This study tries to analyze the political ecological conflicts that arise as a result of the construction of the Jatigede Reservoir in the Sumedang Regency area. To analyze the ecological conflicts that occurred in the construction of the Jatigede Reservoir, researchers used political ecology theory and used research method literature studies, where data was obtained through library sources such as documents and previous research related to the topics and problems studied. The results of this study indicate that there was political ecological conflict in the Jatigede Reservoir development when there was resistance from the community who demanded proper relocation and compensation as compensation for the loss of their homes and fields as their livelihood. In this case it can be seen that the government is trying to carry out economic development to improve people's welfare, but on the other hand it is sacrificing the environment and other communities. The process of constructing this dam has created conflict between the affected communities and the government. Apart from having to lose their homes and places to earn a living, they also lost their ancestral heritage which has become cultural heritage and most of them are the ancestral graves of the Sumedang people and environmental changes have had an impact on the economic decline of the affected people. Key Word : Reservoir, Political Ecology, Politized Environment